Foreign language trainee teachers’ concerns and preparedness to implement inclusive instructional practices with learners with special educational needs: training induced changes - Nijakowska, Joanna (Neofilolog, 2022)
The study was conducted in a group of second year university students – pre-service teachers of English as a foreign language (EFL). The aim of the study was to investigate how the trainee teachers’ participation in a compulsory SEN-dedicated course delivered online impacted their self-reported concerns and preparedness to implement inclusive teaching practices with foreign language (FL) learners with special educational needs (SEN). A semester-long course was designed and conducted as part of emergency remote instruction during the COVID-19 pandemic. Data was collected online via before and after course questionnaires. Principal component analysis of the preparedness and concerns scales led to a two-factor (F1 – self-efficacy beliefs and knowledge and F2 – attitudes) and a single factor solution (concerns) respectively. The pre- (N=113) and post-course (N=86) online survey responses were compared with regard to all the factors. The analysis showed that the participants’ post-course attitudes were more positive than at the beginning of the course, but the difference was not statistically significant. We observed a statistically significant increase in the trainee teachers’ post-course self-efficacy beliefs and knowledge of inclusion and SEN, with a large effect size. This change was paired with a statistically significant increase in their post-course concerns, with medium effect size for the change. A series of one-way MANOVAs showed that the effect of demographic variables (gender, teaching experience other than during practicum, experience with learners with SEN) on all factors across the two datasets was not statistically significant.